Social Accounting Matrices for the Gambia, Liberia, Mauritania and Sierra Leone - Fofana, Ismaël; Balma, Lancia; Traoré, Fousseini; Kane, Dieynaba (International Food Policy Research Institute, 2014)
The report documents the construction of Social Accounting Matrices (SAMs) for The Gambia, Liberia, Mauritania and Sierra Leone. The construction of the SAMs follows the top-down approach. First, aggregated SAMs representing the macro features of the economies are constructed: the macro SAMs. Then, industries, commodities, and institutional accounts are disaggregated with the macro SAMs entries serving as control totals: the micro SAMs. Data sources include national accounts, government financial statistics, balance of payments, and international trade statistics. The result is consistent and balanced 2009 SAMs for The Gambia, Liberia and Mauritania, and a 2008 SAM for Sierra Leone.